2016
DOI: 10.21829/myb.2011.1711155
|View full text |Cite
|
Sign up to set email alerts
|

Germinación y supervivencia de seis especies nativas de un bosque tropical de Tabasco, México

Abstract: rESUMENSe evaluó la germinación y supervivencia in situ y ex situ de plántulas de Aspidosperma megalocarpon, Eugenia sp., Lonchocarpus castilloi, Manilkara zapota, Ormosia macrocalyx y Rollinia mucosa. En campo se sembraron 2 160 semillas en nueve bloques de 5 m x 20 m distribuidos en bosque tropical, acahual maduro y acahual joven. El experimento se replicó en condiciones de vivero bajo sombra de 40, 60 y 80%. Los tipos de cobertura vegetal no mostraron diferencias significativas en las tasas de germinación y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
(16 reference statements)
2
5
0
4
Order By: Relevance
“…Brenan (31.19 % day -1 ) (both Fabaceae). Seeds of O. macrocalyx, tested with no pregerminative treatments, germinated after a 10 -11 day period (Table 1), which represents a relatively short period for this species, although it is similar to that reported by different authors for O. macrocalyx (Sautu et al 2007, Pérez-Hernández et al 2011, Román et al 2012. Different responses have been observed depending on particular species.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Brenan (31.19 % day -1 ) (both Fabaceae). Seeds of O. macrocalyx, tested with no pregerminative treatments, germinated after a 10 -11 day period (Table 1), which represents a relatively short period for this species, although it is similar to that reported by different authors for O. macrocalyx (Sautu et al 2007, Pérez-Hernández et al 2011, Román et al 2012. Different responses have been observed depending on particular species.…”
Section: Discussionsupporting
confidence: 77%
“…Recently formed O. macrocalyx seeds of closed fruits (T1) did not require pregerminative treatments and showed high germination values, as described by Bewley et al (2013) in reference to the seeds contained in recently formed fruits, indicating that they reach physiological maturity followed by an increase in their ability to rapidly germinate, in addition to the fact that the seed coat has still not lignified. Pérez-Hernández et al (2011) found similar results: field and nursery germination was 75 and 87 %, respectively. However, due to the presence of a hard seed coat, the seeds under physical dormancy have germination rates below 1 % (Foster & Delay 1998) or do not germinate at all without a pregerminative treatment (Baskin & Baskin 2004).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations